Predators and eggs parasites of the Diatraea saccharalis of the sugarcane - Degaspari, Nilton; Macedo, Newton; Botelho, Paulo Sérgio Machado; Araújo, José Ribeiro de; Almeida, Luiz Carlos de (Pesquisa Agropecuaria Brasileira, 2014)
The natural control of Diatraea saccharalis eggs was assessed during nearly three successive years, through one-day-old eggs obtained in the laboratory, placed on sugarcane leaves. These eggs returned after 10 days, and the number of eaten up, parasitezed, with dead embryos, viable, and infertile eggs was determined. The population fluctuation of possible egg predators of the sugarcane borer was determined by means of pitfall traps. In this assay it was also attempted to interpret the effects of burning for harvest and for trash elimination on the natural control in the egg phase. It was possible to verify that these practices did not affect the control. The results obtained during the period of studios showed an efficient natural control of D. saccharalis eggs and the predation was the most important factor. Some factors seem to change the behavior of the Trichogramma sp., leading to a low parasitism on eggs Obtained in the laboratory. The percentage of dead embryos environmental temperature and the irrigation of the plantation by aspersion did not influence on the natural control.